2020
DOI: 10.1007/s13595-020-00975-9
|View full text |Cite
|
Sign up to set email alerts
|

The flexural lumber properties of Pinus patula Schiede ex Schltdl. & Cham. improve with decreasing initial tree spacing

Abstract: & Key message An increase in the stiffness of lumber with a decrease in initial tree spacing was confirmed for Pinus patula Schiede ex Schltdl. & Cham. The underlying properties of microfibril angle, wood density and knot frequency explained 71% of the variation in lumber stiffness. Tree spacing also influenced wood properties independent of radial growth rate. & Context Rapid growth rates and reduced harvesting ages of South African-grown pine plantations have caused a reduction in the stiffness of structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The literature reports that several species are more sensitive to this variation. In studies with Pinus patula, tree spacing signifi cantly infl uenced the mechanical properties of wood (Erasmus et al 2018;Erasmus et al, 2020). 11-year-old Pinus radiata forests, planted with high planting densities (2500 stems ha -1 ) had positive eff ects on wood stiff ness in relation to the planting of 833 stems ha -1 .…”
Section: Introductionmentioning
confidence: 99%
“…The literature reports that several species are more sensitive to this variation. In studies with Pinus patula, tree spacing signifi cantly infl uenced the mechanical properties of wood (Erasmus et al 2018;Erasmus et al, 2020). 11-year-old Pinus radiata forests, planted with high planting densities (2500 stems ha -1 ) had positive eff ects on wood stiff ness in relation to the planting of 833 stems ha -1 .…”
Section: Introductionmentioning
confidence: 99%
“…Liziniewicz et al [7] recorded that the mean height of 23-year-old lodgepole pine increased with increasing initial planting density. The initial planting density also affects wood properties, such as basic wood density (BWD) [8][9][10], fiber traits [10], and wood chemical composition [11]. Ahmed et al [12] reported that the planting density influence on growth traits and wood properties is greater than that of the wood chemical composition.…”
Section: Introductionmentioning
confidence: 99%
“…Vaughan et al (2019) showed in Pinus ponderosa that it is not growth rate, per sé, which is closely tied to variation in wood properties (in their case, focussing on wood density as an indicator) but rather annual climate peculiarities which lead to variation in the timing and extent of transitions into latewood production. Erasmus et al (2020), looking at Pinus patula, found a clear effect of tree spacing. This was not just on wood density but also on the less-often measured but critically important, microfibril angle.…”
mentioning
confidence: 99%